Analisis Anggaran Sebagai Kebijakan Salah Satu Alat Pengendalian Kinerja Pada Badan Pengelola Keuangan Dan Aset Daerah (BPKAD) Provinsi Sumatera Utara Kota Medan - Muhammad Dhio Natama Harahap; Saparuddin Siregar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to determine the budget as one of the performance control tools at the Regional Finance and Asset Management Agency (BPKAD) of North Sumatra Province, Medan City. The data collection techniques used were interviews and documentation. The types of data used are quantitative data and qualitative data. The source of data used in this study is secondary data, in the form of Regional Budget Realization Reports. The analysis method used is a comparative descriptive analysis method, namely by comparing the budget with realization in various sources of financing using variance analysis. The results showed that there were irregularities in excess funds of 68.41%, 69.96%, 99.20%, and 32.52% in the budget of BPKAD Medan City for 2022. The conclusion from the analysis and realization of expenditures is that in the 2022 fiscal year, the BPKAD Medan City experienced deviations. Where deviations occur due to the budget that is not absorbed in the budget and expenditure realization. Performance control at the Medan City BPKAD for 2022 is considered good because the budget is greater than the realization in terms of budget variance and expenditure realization variance.